STUDY OF FARMERS HOUSEHOLD FOOD SECURITY: CASE STUDY IN KEBASEN DISTRICT, BANYUMAS REGENCY - Wibowo, Arif Andri; Suharno, Suharno (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2022)
The Covid-19 pandemic has impacted on various economic sectors, one of which is the agricultural sector. This important role of the agricultural sector often ignores the socio-economic conditions of the farmer's household. This research aims to analyze the degree of food security of farmer households during of the Covid-19 pandemic. The method used is the descriptive quantitative method using income and expenditure variables of farmers' households in the last month. The results showed that calculation of the structure of the household income of farmers is dominated by the structure of income from farming by 82.63 %, while the rest comes from non-farming by 17.37 %. Then for the expenditure structure of farmer households, non-food expenditures are greater than food expenditures, which is 59 % compared to food expenditures of 41 %. This gives an understanding that farmers' income is quite high and tends to spend their income to meet needs outside of food (non-food). By using indicators of food security, namely the level of food subsistence and the share of food expenditure, then farmer households in Kebasen District, Banyumas Regency are classified as high or food Unresistant during the Covid-19 pandemic.